The Participation of Indigenous Peoples in the Development of Geographical Indications: Between Orientation and Formulation - Maisa, Maisa; Akbar, Muhammad; Samsuria, Samsuria; Lestiawati, Ida (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Characteristics of Indigenous Peoples in managing this natural potential has relevance to optimizing the potential of geographical indications. Even so, legal problems occur when in positive law in Indonesia there is no regulation regarding the participation and role of the Customary Law Community in optimizing geographical indications.Purpose of The Research: This research aims to regulatory orientation and formulation regarding the participation of Indigenous Peoples in optimizing the potential of geographical indications.Methods of Research: This research is a normative legal research with a concept and statutory approach. The analysis is carried out by carrying out an inventory of legal materials, then proceed with the reduction process (sorting) according to the needs in the selection, and ends with conclusions.Results of the Research: The participation of the Indigenous Peoples in optimizing the potential of geographic indications can actually be carried out by involving the role of both the central and regional governments to facilitate it. Appropriate formulations related to arrangements regarding the participation of Indigenous Peoples in optimizing the potential of geographical indications can be carried out by forming cooperatives or associations of producers related to geographical indications. This needs to be done because in the provisions of positive law, Indigenous Peoples are not one of the parties that can become applicants for registration of geographical indications. Revisions to regulations regarding geographical indications need to be made in order to optimize the role and participation of the Indigenous Peoples.